Corrosion and friction resistance of TiVCrZrWNx high entropy ceramics coatings prepared by magnetron sputtering. Issue 7 (1st April 2022) - Si, Yanxin; Wang, Ganggang; Wen, Mao; Tong, Yang; Wang, Weiwei; Li, Yang; Yan, Linhui; Yu, Wanjun; Zhang, Shangzhou; Ren, Ping
Abstract: High entropy alloy coatings have attracted much attention because of their high hardness, low-level fault energy, and chemical stability. Nevertheless, this type of coating would inevitably suffer from wear, corrosion, aging, and so on. Hence, a novel coating with corrosion and friction resistance would be constructed for broadening its application scenarios. In this work, TiVCrZrWNx high entropy ceramics coatings were prepared by reactive magnetron sputtering. The microstructure, mechanical properties, friction, and corrosion resistance of the coatings deposited at different nitrogen flow rates have been studied. The microstructure of TiVCrZrWNx coatings is strongly dependent on the nitrogen flow rate and forms a stable FCC structure when the nitrogen flow rate reaches 24 sccm. The pure TiVCrZrW coating is 15.65 GPa, with the increase of nitrogen flow rate (24 sccm), the coating hardness reaches 21.27 GPa. The corrosion resistance of the coatings also increases continuously. According to the results of the impedance spectrum and polarization curve, the charge transfer resistance value of the coating gradually increases with the content of nitrogen, the current density rapidly decreases to a minimum as the potential increases. In terms of tribological behavior, the formation of V2 O5 during the sliding in seawater could significantly reduce the coefficient of friction from 0.603 to 0.383. Therefore, TiVCrZrWNx HECs coatings simultaneously possess high hardness, toughness, and excellent resistance to friction and corrosion, which is expected to provide a new and reliable method for the research field of coatings in the maritime field.